Distribution and characteristics of mixed (transitional) mid-Permian (late Artinskian-Ufimian) marine faunas in Asia and their palaeogeographical implications - Guang Shi; NW Archbold; LP Zhan (1995)
The Permian marine biogeography of the Asian region is characterised by the development of three broad realms (Boreal, Tethyan and Gondwanan). In the early Early Permian (Asselian to Early Artinskian), there seems to have existed sharp biogeographical boundaries with no transitional zones between the realms, presumably due to the effect of Gondwanan glaciation and sharp climatic zonation. The mid-Permian (Late Artinskian to Ufimian) of the Asian region is distinguished by the rise of two broad transitional zones in which mixed marine faunas flourished. The northern transitional zone (north and northeast China, Sikhote Alin, central and northeast Japan) is characterised by an admixture of both warm-water Cathaysian and cold temperate Boreal genera. The southern transitional zone (Arabian Peninsula, Iran, Afghanistan, the Karakorum, southeast and central Pamir, Salt Range, central and northwest Tibet, Shan-Thai terrane, Timor, and western Irian Jaya), on the other hand, is distinguished by incorporating faunal elements of both Gondwanan and Cathaysian origin. The mixed faunas of both transitional zones share several antitropically distributed genera (e.g., Monodiexodina, Lytvolasma and Spiriferella) and are succeeded by palaeotropical Tethyan faunas of Late Permian age. It has been postulated that the mixed mid-Permian fauna of the northern transitional zone was probably formed in an epicontinental sea which was connected to both the Asian Tethys and the Arctic, which facilitated the migration of Cathaysian and Boreal forms into the epicontinental sea and subsequent faunal mixing. The formation of the mixed faunas of the southern transitional zone, on the other hand, is probably related to the breaking off of the Cimmerian blocks from northern Gondwana and subsequent drifting into a lower latitudinal zone with geographical proximity to both Gondwana and Cathaysia during the mid-Permian. © 1995 Elsevier Science B.V. All rights reserved.